2015
DOI: 10.1002/bmc.3648
|View full text |Cite
|
Sign up to set email alerts
|

Identification of metabolites of isopropyl 3‐(3,4‐dihydroxyphenyl)‐2‐hydroxypropanoate in rats by high‐performance liquid chromatography combined with electrospray ionization quadrupole time‐of‐flight tandem mass spectrometry

Abstract: Isopropyl 3-(3,4-dihydroxyphenyl)-2-hydroxypropanoate (IDHP) is an investigational new drug having the capacity for treating ailments in cardiovascular and cerebrovascular system. In this work, a rapid and sensitive method using high performance liquid chromatography coupled with electrospray ionization quadrupole time-of-flight tandem mass spectrometry (HPLC-ESI-Q-TOF-MS) was developed to reveal the metabolic profile of IDHP in rats after oral administration. The method involved pretreatment of the samples by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 32 publications
1
4
0
Order By: Relevance
“…Hence, M7a and M7b were speculated to be the glucuronidation products of DSS. Moreover, the specific MS/MS information on M7 was in accordance with an earlier study (Yang et al, ). Based on the statement above, M7a and M7b were putatively assigned as 3‐(3‐hydroxyphenyl‐4‐ O‐ glucuronyl)‐2‐hydroxypropanoic acid and 3‐(3‐ O‐ glucuronyl‐4‐hydroxyphenyl)‐2‐hydroxypropanoic acid (Figure S3).…”
Section: Resultssupporting
confidence: 90%
See 2 more Smart Citations
“…Hence, M7a and M7b were speculated to be the glucuronidation products of DSS. Moreover, the specific MS/MS information on M7 was in accordance with an earlier study (Yang et al, ). Based on the statement above, M7a and M7b were putatively assigned as 3‐(3‐hydroxyphenyl‐4‐ O‐ glucuronyl)‐2‐hydroxypropanoic acid and 3‐(3‐ O‐ glucuronyl‐4‐hydroxyphenyl)‐2‐hydroxypropanoic acid (Figure S3).…”
Section: Resultssupporting
confidence: 90%
“…In addition, the product ion at m / z 211.0603 was consistent with the quasi‐molecular ion of O‐ methylated DSS, according to a previous report (Wang et al, ). The ion at m / z 165.0578 was generated via the loss of HCOOH from the ion at m / z 211.0603 (Yang et al, ), while the fragment ion at m / z 153.1277 was tentatively supposed to be 1 mole of borneol. The information on these ions indicated that the appearance of O‐ methylated DSS was due to the breaking of the ester bond in DBZ to form borneol and DSS, and then O‐ methylation conjugation occurred on one of the hydroxyl groups on the phenyl ring of DSS (Supporting Information, Figure S1).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on the fragmentation pattern, compounds 1 – 2 were previously identified as gallic acid and vanillic acid, respectively [ 21 ]. Compound 3 , reported in Dasya sp., yielded two daughter ions at m/z 179.03 (isopropanol group) and m/z 123.04 by cleaving the α, β carbon–carbon bond, and was identified as isopropyl 3-(3,4-dihydroxyphenyl)-2-hydroxypropanoate [ 37 ]. Compound 4 (3,4-dihydroxyphenylglycol) yielded a precursor ion at m/z 169.0506, which was further fragmented into two major daughter ions at m/z 151.03 (losing H 2 O) and 123.00 (losing CO).…”
Section: Resultsmentioning
confidence: 99%
“…Although there are many studies on the chemical constituents of “Dogel ebs” , at present, it is essential to obtain its pharmacokinetic parameters and metabolism information to fully understand the pharmacological effects and mechanism of “Dogel ebs.” Unfortunately, the identification of metabolites and illustration of its metabolic patterns have not yet been studied, except the pharmacokinetics investigations on matrine , which restricted the therapeutic applications and development of “Dogel ebs.” In order to clarify the metabolic mechanism of “Dogel ebs,” a target‐group‐change couple with mass defect filtering strategy was proposed based on high performance liquid chromatography–quadrupole exactive Orbitrap mass spectrometry (HPLC‐Q‐Exactive/MS) and Compound Discoverer software. As previously reported , Compound Discoverer software could provide elemental composition assignment, exact mass measurement, and fragmentation information in Traditional Chinese medicines and their metabolites in biological matrices .…”
Section: Introductionmentioning
confidence: 99%